Echo's new pet - Hapka, Cathy (New York: Scholastic Inc., 2016)
Pearl has a great time bringing along a baby sea turtle for Show and Tell at dolphin school, but Echo is jealous and set out on a mission to find herself the best pet ever.
550L
Keywords: Dolphins -- Juvenile fiction; Schools -- Juvenile fiction; Magic -- Juvenile fiction; Pets -- Juvenile fiction; Friendship -- Fiction; Schools -- Fiction; Dolphins; Magic; Pets; Schools; Fiction